Perbandingan Harga Dan Volume Saham Farmasi Sebelum Dan Setelah Pengumuman Vaksinasi Covid19 - Deasy Lestary Kusnandar (Universitas Sultan Ageng Tirtayasa, 2021)
The Covid-19 vaccination is one of the Indonesian government's efforts in dealing with the Covid-19 problem. The Covid-19 vaccination aims to create herd immunity so that people become more productive in carrying out their daily activities. This study aims to determine whether there is a significant difference between the stock price and the volume of stock transactions at PT. Indofarma, Tbk and PT. Kimia Farma, Tbk. The research data was taken 30 days before and 30 days after the announcement of the covid 19 vaccination. The data was processed by using the paired sample t test using SPSS Version 20. The results showed that there were significant differences in the volume of stock transactions at PT. Indofarma, Tbk and PT. Kimia Farma, Tbk before and after the announcement of the covid 19 vaccination in Indonesia. Meanwhile, other results show that there is no significant difference in the stock price of PT. Indofarma, Tbk and PT. Kimia Farma, Tbk before and after the announcement of the covid 19 vaccination in Indonesia.